2012
DOI: 10.1021/nn304046m
|View full text |Cite
|
Sign up to set email alerts
|

Using Nanotopography and Metabolomics to Identify Biochemical Effectors of Multipotency

Abstract: It is emerging that mesenchymal stem cell (MSC) metabolic activity may be a key regulator of multipotency. The metabolome represents a "snapshot" of the stem cell phenotype, and therefore metabolic profiling could, through a systems biology approach, offer and highlight critical biochemical pathways for investigation. To date, however, it has remained difficult to undertake unbiased experiments to study MSC multipotency in the absence of strategies to retain multipotency without recourse to soluble factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 46 publications
11
136
0
Order By: Relevance
“…As such, the regulation of FDFT1 directs the formation of either sterol or nonsterol metabolites (21). Although differences in cell metabolic profiles during hMSC commitment and differentiation have been reported previously (22,23), this result represented an unexpected finding because both BG and strontium had been presumed primarily to up-regulate bone formation and/or differentiation of osteoprogenitor cells (7,24).…”
Section: Regulation Of Hmsc Gene Expression By Bg and Srbg Dissolutionmentioning
confidence: 65%
See 1 more Smart Citation
“…As such, the regulation of FDFT1 directs the formation of either sterol or nonsterol metabolites (21). Although differences in cell metabolic profiles during hMSC commitment and differentiation have been reported previously (22,23), this result represented an unexpected finding because both BG and strontium had been presumed primarily to up-regulate bone formation and/or differentiation of osteoprogenitor cells (7,24).…”
Section: Regulation Of Hmsc Gene Expression By Bg and Srbg Dissolutionmentioning
confidence: 65%
“…Moreover, our observation of the increase of active pMLC in the presence of SrBG appeared consistent with the up-regulation of the isoprenoid biosynthesis pathway and demonstrated that strontium incorporation within the BG had an effect on actomyosin activity. This last result is particularly interesting because cytoskeletal arrangement, which is modulated by environmental calcium and strontium (46,47), is known to influence hMSC lineage commitment, particularly during osteogenesis (53), as a result of the modulation of actin/myosin cytoskeletal contraction (40,41,49), and was found to modulate cell metabolic profiles (22). Together, our data suggest that the up-regulation of the mevalonate and sterol biosynthesis pathways in hMSC and subsequent membrane cholesterol and lipid raft enrichment in response to SrBG likely change membrane protein quantity or activity.…”
Section: Discussionmentioning
confidence: 99%
“…This ties in with literature on human MSCs showing that while adipogenesis requires almost no intracellular tension, the MSC growth requires slightly reduced tension than fi broblastic differentiation and much lower tension than osteobalstic differentiation. [ 50,51 ] …”
Section: Discussionmentioning
confidence: 99%
“…By engineering the surface topography of substrates to provide more favorable environments that enhance cell adhesion, growth and proliferation, it may be possible to control essential biological responses. 6,7 Although modulation of cell adhesion and growth using various topographical cues is well studied, most published data address or exploit the topographical confinement that is imposed by the nanostructured architecture. 8,9 In other words, overall control of cellular response is performed by cell isolation in the structure through geometry, and is not influenced by surface topography.…”
Section: Introductionmentioning
confidence: 99%